GM-CSF Quantity Has a Selective Effect on Granulocytic vs. Monocytic Myeloid Development and Function - Sun, Li; Rautela, Jai; Delconte, Rebecca B.; Souza-Fonseca-Guimaraes, Fernando; Carrington, Emma M.; Schenk, Robyn L.; Herold, Marco J.; Huntington, Nicholas D.; Lew, Andrew M.; Xu, Yuekang; Zhan, Yifan (Frontiers in Immunology, 2018)
GM-CSF promotes myeloid differentiation of cultured bone marrow cells into cells of the granulocytic and monocytic lineage; the latter can further differentiate into monocytes/macrophages and dendritic cells. How GM-CSF selects for these different myeloid fates is unresolved. GM-CSF levels can change either iatrogenically (e.g. augmenting leukopoiesis after radiotherapy) or naturally (e.g. during infection or inflammation) resulting in different immunological outcomes. Therefore, we asked whether the dose of GM-CSF may regulate the development of three types of myeloid cells. Here, we showed that GM-CSF acted as a molecular rheostat where the quantity determined which cell type was favoured; moreover, the cellular process by which this was achieved was different for each cell type. Thus, low quantities of GM-CSF promoted the granulocytic lineage, mainly through survival. High quantities promoted the monocytic lineage, mainly through proliferation, whereas moderate quantities promoted moDCs, mainly through differentiation. Finally, we demonstrated that monocytes/macrophages generated with different doses of GM-CSF differed in function. We contend that this selective effect of GM-CSF dose on myeloid differentiation and function should be taken into consideration during pathophysiological states that may alter GM-CSF levels and during GM-CSF agonistic or antagonistic therapy.